An economical non-destructive method for estimating eelgrass, Zostera marina (Potamogetonaceae) leaf growth rates: formal development and use in northwestern Baja California - Soreana Arellano, Elenea; Echeverría Heras, Héctor; Franco Bizcaíno, Ernesto (Revista de Biología Tropical, 2008)
Seagrass beds provide much of the primary production in estuaries; host many fishes and fish larvae, and abate erosion. The present study presents original analytical methods for estimating mean leaf-growth rates of eelgrass (Zostera marina). The method was calibrated by using data collected in a Z. marina meadow at Punta Banda estuary in Baja California, Mexico. The analytical assessments were based on measurements of leaf length and standard regression procedures. We present a detailed explanation of the formal procedures involved in the derivation of these analytical methods. The measured daily leaf-growth rate was 10.9 mm d-1 leaf-1. The corresponding value projected by our method was 10.2 mm d-1 leaf-1. The associated standard errors were of 0.53 and 0.56 mm d-1 leaf-1 respectively. The method was validated by projecting leaf-growth rates from an independent data set, which gave consistent results. The use of the method to obtain the mean leaf growth rate of a transplanted plot is also illustrated. Comparison of our leaf-growth data with previously reported assessments show the significant forcing of sea-surface temperature on eelgrass leaf dynamics. The formal constructs provided here are of general scope and can be applied to equivalent eelgrass data sets in a straightforward manner.